Asistensi Bisnis UMKM Melalui Produksi Konten Media Sosial pada Aledeal Corner - Sari, Serli Ayuneng Indah; Hidayah, Nurul; Asyiqina, Farih Dwi; Safhira, Gena Marcela; Sholehah, Nindi Ummul; Putri, Fitrotul Bita Aulia; Naima, Aina Puspita; Afandi, Akhmad Jazuli (Welfare : Jurnal Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic role in supporting economic growth, including in the food and beverage sector. One of the MSMEs that is developing in this field is Aledeal Corner which focuses on the production and sale of quality food and beverages. However, in the digital era, the main challenge faced by MSMEs is the low utilization of social media for marketing. Therefore, this community service activity aims to increase the visibility and competitiveness of Aledeal Corner through business assistance based on social media content production. The methods used include digital marketing strategy training, creative content production, and assistance in optimizing social media platforms. The results of the activity showed a significant increase in engagement on Aledeal Corner's social media accounts as well as growth in the number of customers. Thus, this program contributes to increasing the competitiveness of MSMEs through effective digital marketing strategies.